PENGELOLAAN KECEMASAN AKADEMIK SISWA MELALUI PELATIHAN REGULASI EMOSI - Irman, Irman (Universitas Islam Negeri Imam Bonjol Padang, 2015)
High academic anxiety will complicate the student to reach academic successfulness. Although in low scale, anxiety is needed by student as motivation in learning. In general, there are two factors that influence academic anxiety, namely instrinsik and ekstrinsik factor. Instrinsik factor among others jender, coping strategy, memory working. Ekstrinsik factor among others style educating of parent, social support, culture.Regulation of emotion as hereinafter factor that influence academic anxiety, having the character of instrinsik and ekstrinsik. At regulation of emotion, student instrinsik factor is triggered by stimulus that given by ekstrinsik factor. According to various literature study, found that anxiety of students’ academic have negative relationship by means of signifikan with regulation emotion. This statement has meaning, excelsior of regulation emotion, progressively go down anxiety of student’s academic. Based on this finding, it can be concluded that training of regulation emotion represent one of the effective intervention to lessen anxiety of students’ academic.